(untitled) (Herald of the National Children’s Medical Center, 2024)
Abstract: This analytical article is devoted to the assistance provided to victims at the scene by persons without medical education. Results of the study: First aid is a set of urgent measures aimed at preserving the life and health of a patient in a critical situation, provided directly by persons with medical skills. On the other hand, first aid is provided by any person until a medical professional arrives at the scene to provide assistance, or until the victim is taken to the hospital by persons without medical education. This type of assistance can be provided by anyone. Conclusion: During natural disasters, rescuers may not be able to quickly meet all your minor medical needs, as they try their best to help only patients with serious injuries or life-threatening conditions.